8. ANALISIS PERFORMA RETORIKA PIDATO GUBERNUR JATENG BIBIT WALUYO DALAM FRAME BALI NDESA MBANGUN DESA - Naryoso, Agus (FORUM, 2014)
Speech manuscripts Central Java Governor About Economic Development in Bali Frame Ndeso Mbangun Deso has presented a tendency to use the portion that is not too long, there is a proportionate balance between the opening, contents and cover other than that displays the title of a good speech, supported by using a lot of supporting data describe rhetoric clear and rational arguments , subtle stylistic choices and be able to express ideas and ideas that touch the actual root cause immediate and potentially be efektf finish.